La qualité de vie au travail dans les établissements sanitaires et médico-sociaux : co-construction d’une méthodologie d’enquête pilotée par la MiRH via un processus participatif - Clémentine Fuchs; Christine Jeoffrion; Sophie Barré; Florence Savary (Perspectives Interdisciplinaires sur le Travail et la Santé)
The aim of this article is to present the approach developed by the MiRH (Human Resources Health Mission - Pays de la Loire) to set up, using a participative process, a method for measuring Quality of Work Life (QWL) in regional health establishments. The approach presented here emphasizes the use and integration of the « Quality of Work Life Barometer » by the concerned actors, which will thereby allow QWL to be mapped in regional health establishments.The participation of 57 health establishments in this study provided us with an interesting view of how the regional establishments complied. It also allowed us to identify the key factors of success and the difficulties to be aware of for those who wish to conduct such a survey.